Evaluation of Sharia-based Sustainability Reporting Framework Influenced by the Emergence of Metaverse Axes in Accounting - Hossein Keshavarzi Nejhad; Maryam Shahri; Vahid Oskou; Mohammad Reza Abdoli (تحقیقات مالی اسلامی (پیوسته))
By promoting jurisprudential values and Shariah standards, Islamic societies are always seeking to strengthen the level of adherence to morality, and this issue has caused many countries to consider Islamic rules in addition to international standards and laws to achieve greater legitimacy. One of these fields in Islamic societies is the issue of Sharia-based sustainability reporting, which has received attention in the past few years. The purpose of this research is evaluation of Sharia-based sustainability reporting framework influenced by the emergence of metaverse axes in accounting. From the point of view of methodology, this study is considered as a combined research that seeks to achieve the research goals based on a set of qualitative and quantitative analysis methods. Therefore, in the qualitative part, through ground theory, the dimensions of Sharia-based sustainability reporting should be identified. Then, based on the systematic content screening process, the axes of the emergence of metaverse in accounting were identified so that in the last part of the qualitative analysis through fuzzy Delphi, the reliability of the identified dimensions of both bases of this study could be confirmed. Then, in the quantitative part, through the Gray VIKOR Matrix, an attempt was made to identify the most effective axis of the emergence of metaverse in accounting to increase the effectiveness of Sharia-based sustainability reporting. The findings of the study in the qualitative part regarding the dimensions of Sharia-based sustainability reporting, indicate the identification of 3 categories; It has 6 components and 41 propositional themes in the form of a multidimensional theoretical framework. Also, in this section, 5 axes of the emergence of metaverse in accounting were identified through systematic content screening, and in the form of fuzzy Delphi analysis, all dimensions were confirmed. In the quantitative part, the result indicates the determination of the development of the data mining process in accounting analysis as the most central influence on the dimension of adherence to Sharia ethics in sustainability reporting. The obtained results indicate that Sharia-based sustainability reporting can lead to the grounding of anti-corruption social behaviors and Islamic financing methods in companies' strategies and thus provide higher accountability to stakeholders.